ANALISIS COST-VOLUME-PROFIT (CVP) UNTUK PERENCANAAN LABA PADA PT SAKA AGUNG ABADI DI SAMARINDA - Murfat Effendy, Nindy Pratiwi Elfreda Aplonia lau (EKONOMIA, 2016)
The purpose of this study is to determine the level of break-even point that PT Saka Agung Abadi did not suffer losses and analyze the sales rate how PT Saka Agung Abadi can achieve profit increase of 20%. The analytical tool used in this research is the analysis of Cost-Volume-Profit (CVP), which includes the analysis of Break Even Point Analysis and Profit Planning. Data obtained using the techniques of documentation and observation.PT Saka Agung Abadi is a company engaged in the cement manufacturing industry. Type production is portland cement, white cement, and cement mix. Based on the results of research conducted on the sales report and cost of PT Saka Agung Abadi was found that the break even point for 2015 in rupiah at Rp33,402,243,293 and the unit amounted to 516 546 units. The results of the profit to be obtained by the company in 2016 by targeting terjadikenaikan by 20% from last year's profit is 284 595 406. The results of the calculation of the level of sales to be achieved. Tingkatpenjualan calculation results to be achieved in supporting the planning of the targeted profit amounted Rp284.595.406 sebelumnyayaitu amounted Rp37.511.783.347. Assuming that the company's 2016 sale price and the total costs incurred are likely to remain unchanged or hypothesis accepted.